Preventive effect of toothpastes with MMP inhibitors on human dentine erosion and abrasion in vitro - Angelica Reis Hannas; Melissa Thiemi Kato; Cristiane de Almeida Baldini Cardoso; Ana Carolina Magalhães; José Carlos Pereira; Leo Tjäderhane; Marília Afonso Rabelo Buzalaf (University of São Paulo, 2016)
ABSTRACT The use of gels and mouthrinses with MMP inhibitors (chlorhexidine, and green tea extract) was shown to prevent erosive wear. The aim of this study was to analyze the protective effect of toothpastes containing MMP inhibitors on dentine loss induced by erosion in vitro. Material and Methods Five groups each containing 12 specimens of human root dentine were prepared. The specimens were subjected to 1 min erosion by immersion in a cola drink, 4 times a day, for 5 d. Each day, after the first and last erosive challenges, the specimens were brushed for 15 s with a slurry of dentifrice and water (1:3) containing placebo, 1,100 ppm fluoride, 0.61% green tea extract, 0.12% chlorhexidine or 0.004% chlorhexidine (commercial toothpaste). Between the acid challenges, the specimens were stored in artificial saliva with remineralizing potential until the next treatment. Dentine loss was determined using profilometry. Data were analyzed using one-way ANOVA after log transform (p<0.05). Results The mean wear values (μm) were as follows: placebo 1.83±0.53; 0.61% green tea extract 1.00±0.21; fluoride 1.27±0.43; 0.12% chlorhexidine 1.19±0.30; and 0.004% chlorhexidine 1.22±0.46. There was a significant difference in wear between placebo and all the treatment toothpastes, which did not differ from each other. Conclusion The results suggest that toothpastes containing MMP inhibitors are as effective as those based on NaF in preventing dentine erosion and abrasion.